Metode Pengembangan Sumber Daya Manusia melalui Pendidikan dan Pelatihan di SMAN 1 Setu Kabupaten Bekasi - Rosulinawati Lina; Irnie Victorynie; Riyanto Riyanto; Maman Saepulloh (Transformasi Manageria Journal of Islamic Education Management, 2025)
ABSTRACT The purpose of this study was to analyze the methods of human resource development applied at SMAN 1 Setu, and to identify the challenges and opportunities faced in its implementation. The research method used a descriptive qualitative approach. The results of the study showed that human resource development through education and training at SMAN 1 Setu, Bekasi Regency, had a positive impact on improving the quality of teaching and teacher competence. With various methods applied, such as competency-based training, utilization of technology, and collaboration between educators, SMAN 1 Setu succeeded in improving the professional skills of teachers in various aspects. The challenges of limited budget and time are still obstacles that need to be solved. Human resource development in schools will be more optimal if supported by various related parties. Keywords: development, human resources, education, training, teaching staff ABSTRAK Tujuan penelitian ini untuk menganalisis metode-metode pengembangan SDM yang diterapkan di SMAN 1 Setu, serta mengidentifikasi tantangan dan peluang yang dihadapi dalam pelaksanaannya. Metode penelitian menggunakan pendekatan kualitatif deskriptif. Hasil penelitian menunjukkan bahwa pengembangan SDM melalui pendidikan dan pelatihan di SMAN 1 Setu Kabupaten Bekasi berdampak positif dalam meningkatkan kualitas pengajaran dan kompetensi guru. Dengan berbagai metode yang diterapkan, seperti pelatihan berbasis kompetensi, pemanfaatan teknologi, serta kolaborasi antar tenaga pendidik, SMAN 1 Setu berhasil meningkatkan keterampilan profesional guru dalam berbagai aspek. Tantangan keterbatasan anggaran dan waktu masih menjadi hambatan yang perlu dicari solusinya. Pengembangan SDM di sekolah-sekolah semakin optimal apabila didukung berbagai pihak terkait. Kata kunci: pengembangan, sumber daya manusia, pendidikan, pelatihan, tenaga pendidik